KOH-activated high surface area Douglas Fir biochar for adsorbing aqueous Cr(VI), Pb(II) and Cd(II). (April 2021) - Herath, Amali; Layne, Cody A.; Perez, Felio; Hassan, EI Barbary; Pittman, Charles U.; Mlsna, Todd E.
Abstract: Biochar has become a popular research topic in sustainable chemistry for use both in agriculture and pollution abatement. To enhance aqueous Cr(VI), Pb(II) and Cd(II) removal efficiency, high surface area (535 m 2 /g) byproduct Douglas fir biochar (DFBC) from commercial syn-gas production obtained by fast pyrolysis (900–1000 °C, 1–10 s), was subjected to a KOH activation. KOH-activated biochar (KOHBC) underwent a remarkable surface area increase to 1049 m 2 /g and a three-fold increase in pore volume (BET analysis). Batch sorption studies on KOHBC verses pH revealed that the highest chromium, lead and cadmium removal capacities occurred at pH 2.0, 5.0 and 6.0, respectively. KOHBC exhibited much higher adsorption capacities than unactivated DFBC. Heavy metal loadings onto KOHBC were characterized by scanning electron microscopy, transmission electron microscopy and X-ray photoelectron spectroscopy. Sorption of Cr(VI), Pb(II) and Cd(II) all followed pseudo-second order kinetics and the Langmuir adsorption model. The highest Langmuir adsorption capacities at the respective pH's of maximum adsorption were 140.0 mg g −1 Pb(II), 127.2 mg g -1 Cr(VI) and 29.0 mg g −1 Cd(II). Metal ions spiked into natural and laboratory waste water systems exhibited high sorption capacities. Desorption studies carried out using 0.1 M HCl revealed that Pb(II) adsorption onto the KOHBC surface is reversible. Portions of Cd(II) and Cr(VI) adsorbed strongly onto KOHBC were unable to be desorbed by 0.1 M HCl and 0.1 M NaOH. Graphical abstract: Image 1 Highlights: KOH activation remarkably increased the biochar surface area from 535 to 1050 m 2 /g. KOH activation of DFBC improved Cr(VI), Pb(II) and Cd(II) removal from natural and wastewater systems. Adsorption followed pseudo-second order kinetics reaching equilibrium within 2 h. High adsorption capacity was contributed to chelation, electrostatic-attraction, and ion exchange mechanisms. KOHBC was recycled thrice while maintaining 75, 50 and 54% of its adsorption capacity for Cr(VI), Pb(II) and Cd(II).